Strategi Peningkatan Kesadaran Pertanian Berkelanjutan di Desa Japanan Melalui Pendampingan Pembuatan Pupuk Organik - Nurul Aini P; Efrilia Lukita S; Dwi Selvi A; Umi Nur F; Fatma Mirrohmatil M; Ramadhani Mahendra K (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Field Study and Community Service is a community service program which is a form of implementation of the Tri Dharma of Higher Education. One area that is often focused on in KKN is agriculture. Agriculture in Indonesia still faces various problems, one of which is farmers' dependence on the use of chemicals as fertilizers and pesticides. The use of chemicals in agriculture can have long-term negative impacts such as damage to soil structure. One approach that can be applied is the use of animal waste as a natural ingredient in making organic fertilizer. Through Field Study and Community Service program, outreach and training is provided to the community regarding techniques for using animal waste as organic fertilizer. This activity was carried out using methods starting from surveys, outreach, and practice of processing goat manure waste into organic fertilizer. Socialization accompanied by direct practice can provide farmers with more knowledge to understand and apply techniques for making organic fertilizer more effectively. In addition, the use of organic fertilizer can reduce farmers' dependence on chemical fertilizers, increase soil fertility, and optimize agricultural yields.